Application of shock blasting mode in mine roadway construction - Mineev, S.; Yanzhula, O.; Hulai, O.; Minieiev, O.; Zabolotnikova, V. (Розробка родовищ, 2016)
Purpose.Working out measures providing safe application of a shock blasting mode while driving workings in outburst-prone coal seams. Methods. Conveying of shock blasting at the mine workings on the coal mines of Ukraine is regulated by a number of specification documents. At the same time, in the process of shock blasting production numerous technological violations of the mode take place and there are often gas-dynamic phenomena, including those with death of people. The mode of shock blasting at mines is used for unworked coal breaking on outburst-prone seams regardless of results of prognosis and efficiency of antilanding measures done, at troublesome seams in the zones where the reading “prone” is set by latest estimate; and while driving in outburst-prone coal seams. Findings. Shock blasting is used at mines at mines in rather wide range of mining and geological conditions. It is recommended to apply the methods of intensity and frequency of gas and oil emissions attenuation at shock blasting on especially outburst-prone layers. The methods of depth increase of pre-face part of a coal bed unloading zone are used. The increase is achieved by means of heading rock loosening of adjacent strata, advanced blasting, blast hole charge operation in adjacent strata, front-rank loosening (camouflet blasting) of coal bed. Moreover, the blasting pattern with formation of piled blocking retaining wall is applied.